2018
DOI: 10.1002/jcph.1363
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and Prevention of CMV Disease in Transplant Recipients: Current Knowledge and Future Perspectives

Abstract: This review summarizes the significant impact of cytomegalovirus (CMV) infection on solid organ and hematopoietic stem cell transplant recipients. A discussion of the various CMV prevention and treatment strategies is provided, including a detailed description of each of the available CMV antiviral drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 121 publications
0
7
0
Order By: Relevance
“…However, HCMV can acquire Letermovir resistance in vitro [31] and in patients [32]. The resistance was associated with mutations in UL56 and to lesser extend in UL89 or UL51 [33,34]. Due to these limitations, we are convinced that additional treatment options and drug targets are urgently needed.…”
Section: The Human Cytomegalovirusmentioning
confidence: 99%
“…However, HCMV can acquire Letermovir resistance in vitro [31] and in patients [32]. The resistance was associated with mutations in UL56 and to lesser extend in UL89 or UL51 [33,34]. Due to these limitations, we are convinced that additional treatment options and drug targets are urgently needed.…”
Section: The Human Cytomegalovirusmentioning
confidence: 99%
“…For cases who were detected Cytomegalovirus 22 and Human gammaherpesvirus 4 23 by mNGS, if serum PCR indicated positive at the same time, we identified that they were infectious pathogens. Furthermore, the mixed infection was defined as the isolation of more than one pathogenic species.…”
Section: Methodsmentioning
confidence: 99%
“…Because of the non-specificity of clinical symptoms caused by CMV infection, laboratory examination is the main basis for the diagnosis of CMV infection. The most two widely used clinical methods are CMV virus replication and serum immunological methods including the detection of CMV IgG, CMV IgM and CMV antigen PP65 (2) In patients with impaired immune function, the production of CMV antibody is weakened or delayed, which may lead to false negative and increase the rate of missed diagnosis, therefor PCR detection of CMV-DNA has largely become the standard method for diagnosis of CMV infection and monitoring of treatment (3). Daisuke Mizushima et al reported that plasma CMV-DNA PCR has important value in the diagnosis for both CMV retinitis and all CMV-EOD in patients with advanced HIV-1 infection (4).…”
Section: Introductionmentioning
confidence: 99%